Establishing a Sickle Cell Disease Registry in Africa: Experience From the Sickle Pan-African Research Consortium, Kumasi-Ghana - Paintsil, Vivian; Amuzu, Evans Xorse; Nyanor, Isaac; Asafo-Adjei, Emmanuel; Mohammed, Abdul Razak; Yawnumah, Suraj Abubakar; Oppong-Mensah, Yaa Gyamfua; Nguah, Samuel Blay; Obeng, Paul; Dogbe, Elliot Eli; Jonas, Mario; Nembaware, Victoria; et al. (Frontiers in Genetics, 2022)
Sickle Cell Disease (SCD) is the most common clinically significant hemoglobinopathy, characterized by painful episodes, anemia, high risk of infections, and other acute and chronic complications. In Africa, where the disease is most prevalent, large longitudinal data on patients and their outcomes are lacking. This article describes the experiences of the Kumasi Centre for SCD at the Komfo Anokye Teaching Hospital (KCSCD-KATH), as a Sickle Pan-African Research Consortium (SPARCO) site and a SickleInAfrica Consortium member, in establishing a SCD registry for the evaluation of the outcomes of patients. It also provides a report of a preliminary analysis of the data. The process of developing the registry database involved comprehensive review of the center’s SCD patient medical records, incorporating data elements developed by the SickleInAfrica Consortium and obtaining ethical clearance from the local Institutional Review Board. From December 2017 to March 2020, 3,148 SCD patients were enrolled into the SCD registry. Enrolment was during the SCD outpatient clinic visits or through home visits. A significant proportion of the patients were from the newborn screening cohort (50.3%) and were males (52.9%). SCD-SS, SCD-SC and Sβ +-thalassemia were seen in 67.2%, 32.5% and 0.3% patients respectively. Majority of the patients were in a steady state at enrolment; however, some were enrolled after discharge for an acute illness admission. The top two clinical diagnoses for SCD-SS patients were sickle cell painful events and acute anemia secondary to hyper-hemolysis with incidence rates of 141.86 per 10,000 person months of observation (PMO) and 32.74 per 10,000 PMO respectively. In SCD-SC patients the top two diagnosis were sickle cell painful events and avascular necrosis with incidence rates of 203.09 per 10,000 PMO and 21.19 per 10,000 PMO respectively. The SPARCO Kumasi site has developed skills and infrastructure to design, manage and analyze data in the SCD registry. The newborn screening program and alternative recruitment methods such as radio announcement and home visits to defaulting patients were key in enrolling patients into the registry. The registry will provide longitudinal data that will help improve knowledge of SCD in Ghana and Africa through research.